The Political Economy of State and Local Investment in Pre-K Programs - Matthew E. Kahn; Kyle Barron (Institute for the Study of Labor (IZA), 2015)
The expansion of access to publicly provided pre-kindergarten bundles together redistribution to the poor with an early human capital investment. Financing publicly provided pre-K investment is mainly a state and local issue. Which voters favor local pre-K expansion? This paper uses several new data sets to describe the circumstances such that local voters reveal a willingness to spend on an early intervention that may not yield direct benefits for them. Republican voters consistently oppose the expansion of publicly provided pre-K. Suburban voters also tend to oppose such investment. We explore several possible explanations for these facts.
Keywords: H41; 330; early childhood investment; voting; urban; suburban